(untitled) (Bangladesh Pharmaceutical Journal, 2016)
The aim of present investigation was to formulate and evaluate the sustained release matrix tablets of Repaglinide (RPGN). These matrix tablets were prepared by wet granulation method using synthetic and natural polymers like HPMC K4M, HPMC 100M and Guar gum (GG), Carrageenan (CG), respectively. Invitro drug release studies were performed by USP dissolution apparatus type-II (paddle method) using 0.1 N HCl buffer and pH 6.8 phosphate buffer for 12 h. Amongst all the 12 formulations, formulation F12 showed maximum drug release of 97.9% for 12 h study. It was observed from the kinetic studies that all the formulations followed first order kinetics and particularly the drug release from its dosage form was fickian diffusion (F9, F12), non-fickian diffusion (F1-F8, F10-F11). Formulation F12 was subjected to stability studies and confirmed that formulation F12 was stable upto the period of 1 month. Bangladesh Pharmaceutical Journal 19(1): 92-99, 2016